ANALYSIS OF THE BOOK AṢĀLĪBU AR-RASŪL ṢALLALLĀHU ʿALAIHI WA SALLAMA FĪ AD-DA‘WAH WA AT-TARBIYAH: THE RELEVANCE AND CONTEXTUALISATION OF THE PROPHET MUḤAMMAD’S METHODS OF DA‘WAH AND EDUCATION IN THE FORMAL EDUCATION SYSTEM - Rahman, Aziz; Fahrurrozi (LPPM UIN Syekh Wasil Kediri, 2025)
This study aims to examine and analyse the methods of preaching and education applied by the Prophet Muhammad SAW in the book Aṣālību ar-Rasūl Ṣallallāhu ʿAlaihi Wa Sallama fī ad-Da‘wah wa at-Tarbiyah to reveal their relevance and contextualisation with formal education today. The method used in this study is a descriptive qualitative approach with text analysis, which aims to contextualise the values of the Prophet Muhammad's (peace be upon him) methods of preaching and education in today's formal education system. The researcher found three important points outlined in the book. First, the nature and characteristics of the Prophet consist of eight traits, namely: compassion, patience, intelligence, humility, generosity, forgiveness, integrity of character, and love for his profession. Second, the methods of da'wah used by the Prophet Muhammad SAW, such as the strategy of giving, the strategy of gifts, and the strategy of sending letters. Third, the Prophet's educational methods included lectures and hands-on practice, motivating students, active learning through question and answer methods, fostering emotional bonds between educators and students, paying attention to students' physical and psychological development, and instilling the value of ukhuwah (brotherhood). The results of this study show that the methods of da'wah and education used by the Prophet Muhammad SAW are relevant for application in modern formal education systems.